Biogenerator for a Cocoa Farm - Jorge Henrique de Oliveira Sales; Rafaela Cristina Ferreira Brito (The Journal of Engineering and Exact Sciences)
Biomass presents itself as a technological solution with great potential for generating energy. In this context, this work aims to develop the analysis of a rural biodigester for the production of electric energy in a cocoa farm, proposing a Marine-type model as a study reference and its production of biogas as a source of electric energy. The energy feasibility verification parameters are analyzed in relation to the energy generation system, considering a biogas load of 163 m3 per day. The technical potential for generating electricity for the chosen system suggests the supply of electricity demand with a large margin for the energy autonomy of the property.